Obesity Fact Sheet in Korea, 2018: Data Focusing on Waist Circumference and Obesity-Related Comorbidities - Nam, Ga Eun (J Obes Metab Syndr, 2019)
BACKGROUND: The global prevalence of obesity has increased steadily in recent years. Waist circumference (WC) reflects body composition better than body mass index. The Korean Society for the Study of Obesity released the 2018 Obesity Fact Sheet to address the incidence of obesity-related comorbidities according to WC levels. METHODS: Data from the Korean National Health Insurance Service health examination database from 2009 to 2016 were analyzed. Abdominal obesity was defined as a WC ≥90 cm in men and ≥85 cm in women. Incidence rates of comorbidities and all-cause mortality rates were calculated after standardizing by age and sex based on the 2010 census. RESULTS: From 2009 to 2015, the incidence rates of type 2 diabetes mellitus, hypertension, myocardial infarction, and ischemic stroke increased both in men and women. Individuals with the lowest WC levels had the highest all-cause mortality rates followed by those with the highest WC levels in men, women, and the total population. The incidence rates of total cancer increased as WC levels escalated between 2009 and 2016. In men, the incidence rates of colorectal, prostate, and liver cancers increased as WC levels increased. The incidence rates of thyroid, colorectal, and stomach cancers increased as WC levels rose in women. In addition, medical expenses continuously increased as WC increased in both men and women. CONCLUSION: Based on the 2018 Obesity Fact Sheet, strategies for reducing the abdominal obesity and related comorbidities and medical expenses are a public health priority.